CONSUMER BEHAVIOR ANALYSIS OF PURCHASE DECISIONS AND CUSTOMER SATISFACTION WHO BUYS FASHION PRODUCTS THROUGH TRANSACTIONS VIA MARKETPLACE IN JEMBER DISTRICT - Nursyamsida Tohari; Nike Norma Epriliyana (MBA - Journal of Management and Business Aplication, 2023)
This study aims to analyze consumer behavior towards purchase decision via the marketplaceand consumer satisfaction in Jember Regency. After the covid-19 pandemic, the marketplace isgrowing and offering a variety of services that can satisfy its consumers. The researchrespondents consisted of 150 marketplace user respondents, namely Bukalapak, Shoppee,Tokopedia, Lazada, and Blibli. Data collection techniques consist of e-questionnaire. Dataanalysis using path analysis. Research variables consist of exogenous trust variable (X1); Price(X2); Convenience (X3); Reference Group (X4); Quality of Information (X5). The endogenousvariable is consumer satisfaction (Y). The intervening variable is the purchase decision (Z). Theresults of the study concluded that the Trust Variable (X1) had no significant effect on consumerdecisions (Z) as evidenced by the results of hypothesis testing with values of sig. 0.130 and0.114; Price variable (X2) has a significant effect on consumer decisions (Z) as evidenced by theresults of hypothesis testing with values of sig. 0.000 and 0.205; The convenience variable (X3)has a significant effect on consumer decisions (Z) as evidenced by the results of hypothesistesting with values of sig. 0.000 and 0.216; The Reference Group variable (X4) has nosignificant effect on consumer decisions (Z) as evidenced by the results of hypothesis testingwith values of sig. 0.047 and 0.160; Quality of Information variable (X5) has a significant effecton consumer decisions (Z) as evidenced by the results of hypothesis testing with values of sig0.130 and 0.114; The Consumer Decision Variable (Z) has a significant effect on consumersatisfaction (Y) as evidenced by the results of hypothesis testing with a value of sig. 0.000 and0.494.